Systemy innowacji jako element regionalnej polityki innowacyjnej - Grzybowska, Barbara (Innovation Systems as an Element of Regional Innovation Policy, 2009)
Reflection of the systemic innovation at the macroeconomic level are the national innovation systems, whereas mezo-economic approach represents a regional systems (RSI). RSI are one of the most important instruments of regional innovation policy. Innovation policy in Poland at the mezo-level is not fully formed. This is due to the relatively limited interest in the problems of innovation at the level of the region in earlier years and at the same time a short period of operation of the regional innovation strategy. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 585-592